Bank Shots: Dude Perfect, Corporatization, and Sporting [Hyper‐]Reality. (13th October 2014) - Bunds, Kyle S.; Newman, Joshua I.; Proffitt, Jennifer M.
<x xml:space="preserve">Abstract</x> This article investigates the paradoxes of communicative liberalization. We explore the ways in which something as seemingly banal as backyard basketball—by being incorporated into the realm of Internet communication—is at once "opened up" to the media consuming public and yet invariably constrained by the corporate and spectacularizing technologies that have come to define the era of free market communication. Drawing upon an extensive case analysis of the "trick shot" enterprise known as Dude Perfect, we illustrate how even the most homespun forms of mediation are thrust into the imperatives of neoliberal accumulation whereby the "homemade" cyber‐spatial media‐sport production becomes aligned with, if not overdetermined by, the processes of corporatization, spectacularization, and marketization.